Documenting Maritime Heritage at Risk Digital Tools, Communities, and Institutions - Shotton, Elizabeth; Prizeman, Oriel (Taylor & Francis, 2024)
Documenting Maritime Heritage at Risk addresses the risks posed to coastal piers and quays due to climate change, the urgent need for documentation and attendant questions regarding long-term conservation, and the role communities could have in this endeavour. Case studies from communities, researchers, and national agencies offer insights into the documentation and analysis of coastal heritage, guidance on survey methodologies, and the potential of digital tools. Communities living along the coast, who are deeply attached to their heritage, are facing these threats very directly - and often with a sense of having little agency in the discussions or decisions being taken. Yet, as the book demonstrates, they could have a central role to play as first-hand observers of the impact of climate change on their heritage. The collection offers an overview of the invaluable role of different participants, working collectively in the documentation and management of endangered maritime heritage. Documenting Maritime Heritage at Risk provides a vital resource for researchers and students engaged in the study of maritime heritage. It will also be of great interest to practitioners, such as local heritage or conservation officers and marine engineers who bear the primary responsibility for recording and maintaining maritime heritage.